2000
DOI: 10.1055/s-2000-9642
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Increases Leukocyte Granule Release During Simulated Extracorporeal Circulation1

Abstract: Nitric oxide increased release of leukocyte granule derived proteins; MPO and HNL at an early stage of simulated extracorporeal circulation. At the same time, nitric oxide did not affect the whole blood and leukocyte capacity to produce oxygen free radicals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
1
4
1
Order By: Relevance
“…We have previously observed that addition of NO during three hours long SECC did not affect leukocyte granule release, but in a later experiment with 23 h SECC, we found increased secretion of MPO and HNL [4,14]. Increased release of leukocyte-derived proteins, MPO, LF and HNL with the addition of 80 ppm of NO to the circuit in this study confirms the findings from our earlier experiment when 40 ppm of NO was added.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…We have previously observed that addition of NO during three hours long SECC did not affect leukocyte granule release, but in a later experiment with 23 h SECC, we found increased secretion of MPO and HNL [4,14]. Increased release of leukocyte-derived proteins, MPO, LF and HNL with the addition of 80 ppm of NO to the circuit in this study confirms the findings from our earlier experiment when 40 ppm of NO was added.…”
Section: Discussionsupporting
confidence: 89%
“…Blood samples (4 ml) for oxygen free radical measurements in whole blood and isolated granulocytes were taken into tubes with 15 IU sodium heparin. Granulocyte isolation was performed according to previously described methods [4,7]. The total amount of samples taken from the circuit amounted to 20 ml at each time point.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is consistent with findings from another working group [21], who also did not report ECC-induced changes of cell counts except for changes associated with hemodilution. In contrast, other authors reported significant decreases in white blood cell and platelet counts [13] during ex vivo ECC [16][17][18]22]. These changes were interpreted as being caused by white blood cell and platelet adhesion to the surfaces of the ECC circuit.…”
Section: Discussionmentioning
confidence: 61%